Evaluation of microbial quality and safety of selected dairy products with special focus on toxigenic genes of Bacillus cereus - Adam, A.H (Array, 2021)
Although dairy products play a significant role in human nutrition, they may cause a risk to the consumers. This study intends to determine the microbial contamination level in selected milk products concerning Bacillus cereus enterotoxigenic genes. Three hundred plant-origin flavoured cheese, flavoured yogurt, flavoured drinking yogurt, kareish (skim milk cheese), soft cheese, and Ras (Romy) cheese (50 samples for each) were randomly collected from retail markets at different districts in El Fayoum Governorate, Egypt. The microbiological analysis and the molecular identification of Bacillus cereus by multiplex PCR were applied and revealed potential risks associated with consumption of the tested milk products (white soft, Ras, and kareish cheeses). In all analysed cheeses (white soft, Ras and kareish) a high contamination level with coagulase positive staphylococci (20.0 %, 22.0 % and 20.0 %) and coliform bacteria (76.0, 86.0, and 88.0 %) was detected. The highest percent (78.0 %) of fungi was found in kareish cheese samples. Bacillus licheniformis was the most aerobic spore forming bacteria detected in kareish cheese (23.7 %) and flavoured drinking yogurt (17.0 %) samples. The highest prevalence (8.0%) of Bacillus cereus was recorded in the flavoured drinking yogurt and white soft cheese samples. The (nhe) was the most detected gene (100.0 %) in all of the examined samples.